Symbolism in Charles Dickens’s Oliver Twist (1837-9): A critical study - Hillis, Rajaa Radwan (Journal of Humanities & Social Sciences, 2021)
When Charles Dickens wrote Oliver Twist in the 1830s, poverty and crime were huge problems in London. To highlight these problems throughout his novel, the author used various literary techniques to create an interaction between the reader and the text in which text can have multiple meanings that can shift over the time. Thus, he uses symbols to evoke a range of additional meaning and significance. His purpose is to get the reader’s attention to construct meaning as the plot progress to what he intends to communicate about innocent individuals or villainous ones. Symbolism, irony, and satire were among the tools he used in his work. They work together to convey a deeper embedded meaning to cast suggestions about the development of the novel to emphasize the point the author seeks to stress throughout the novel. Drawing upon the importance of literary devices in unfolding the thematic concerns of the novel, this paper seeks to run an in-depth analysis of how symbolism played a vital role throughout Oliver Twist. The paper argues that through symbolism, the author channels meaning in Oliver Twist to develop the thematic concerns of the novel in creative ways to shape the reader’s response and to create a strong bond between the reader and the text. The paper argues that literary symbolism in Charles Dickens’s novel is based on evoking the mental image in the reader’s mind to structure meaning through his/her interaction with the text and then shaping his response according to his/her experience. It also creates a strong bond between the reader and the text.